Vegetable farmers' perception of wastewater use in Ojoo Local Government Area (LGA) of Lagos State (2009)
In Nigeria, as in many other countries, wastewater use in agricultural production by farming households is on the rise and there is a need to draw the attention of key players and urban authorities in fostering appropriate planning initiatives. For this reason, the perception and knowledge of vegetable farmers becomes necessary to improve their production activities and yield. While previous studies have confirmed limited or no awareness information and education to vegetable farmers that engage in wastewater dependent activities there has been less attention to the perception and knowledge of vegetable farmers' use of wastewater. The purpose of this study was to examine wastewater use in vegetable production as perceived by 200 randomly selected farmers in Ojoo LGA in Lagos State. Results indicate significant relationship between farmers' perception and knowledge of wastewater use across 32 perceptual and 22 knowledge dimensions. Respondents' have high perception (96.3%) and knowledge (53.0%) of wastewater use in vegetable production. Regular challenges experienced by these farmers are environmental pollution, fire and disease outbreaks, disputes, and pest infestation while occasional ones include drought, erosion, flood, climatic fluctuations, and unstable market prices.